Correction: Synthesis and biological evaluation of N-(4-phenylthiazol-2-yl)cinnamamide derivatives as novel potential anti-tumor agents. Issue 7 (8th July 2015) - Luo, Yong; Zhu, Yongxia; Ran, Kai; Liu, Zhihao; Wang, Ningyu; Feng, Qiang; Zeng, Jun; Zhang, Lidan; He, Bing; Ye, Tinghong; Zhu, Shirui; Qiu, Xiaolong; et al.
<x xml:space="preserve">Abstract</x> Correction for 'Synthesis and biological evaluation of N-(4-phenylthiazol-2-yl)cinnamamide derivatives as novel potential anti-tumor agents' by Yong Luo et al., Med. Chem. Commun., 2015, 6, 1036.